(untitled) (Bangladesh Journal of Nuclear Medicine, 2026)
Primary malignant mesenchymal tumors are heterogenous group of tumors arising from bone, cartilage and other connective tissues. The aggressive nature of these tumors requires prompt diagnosis and multidisciplinary approach for best possible outcome for the patients. Bone scintigraphy being an excellent modality to detect osteoblastic bone activity can help in early detection of primary bone tumors as well as staging, localizing of lesion and aiding in multidisciplinary management alongside other imaging facilities. The reported case demonstrates a 22-year-old male patient with pain and swelling in left hip and upper thigh for four months. Initial radiograph revealed a large expansile mixed lytic and sclerotic lesion of femur. However, bone scintigraphy precisely localized the lesion involving femoral head and proximal part, excluding any distant skeletal metastasis. Finally, histopathological findings confirmed the tumor to be a malignant one with mesenchymal origin, likely an Osteosarcoma. This case once again proves that nuclear medicine techniques including 99mTc -MDP Bone Scintigraphy has now become an integral part for diagnosing and staging of primary malignant mesenchymal tumors alongside conventional radiographs. Bangladesh J. Nuclear Med. 28(2): 390-393, 2025